Flourish by Design - Dunn, Nick; Cruickshank, Leon; Coupe, Gemma (Taylor & Francis, 2024)
Flourish by Design brings together a range of established and emerging voices in design research for a collection that provides original provocations on topics of global significance. It is an insightful guide to original theory and practice concerning how we can design for a better tomorrow. Featuring contributors from a diverse array of backgrounds and professions, this edited book explores the difference that design and design research can make for people, organisations, and the planet to prosper now and in the future. It offers a range of ideas and techniques through practical examples and ongoing projects showing how applied design research can respond to global challenges. Covering topics as diverse as artificial intelligence, bio-inspired materials, more-than-human design, sustainability, and urban acupuncture, it shares interdisciplinary and transdisciplinary design research not just to demonstrate what could be plausible in the near future but also to explain why it might be preferable. By sharing these despatches, this collection represents the very best of what design research can do, explaining how and why. This book is intended for a wide audience of professionals, scholars, and students in design, architecture, and public policy, as well as anyone who has an interest in how we design the world and, in turn, it designs us.